2004
DOI: 10.1095/biolreprod.103.022822
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate Is Required for Migration of Sperm Epididymal Protein DE (CRISP-1) to the Equatorial Segment and Expression of Rat Sperm Fusion Ability1

Abstract: Numerous studies have demonstrated that sperm capacitation is a bicarbonate-dependent process. In the rat, capacitation has not been studied as much as in other species, mainly because of the difficulties in carrying out functional assays with this animal model. In the present study, we have examined the influence of bicarbonate in the overall rat sperm capacitation process by analyzing involvement of the anion in 1) protein tyrosine phosphorylation, 2) migration of epididymal protein DE (also known as CRISP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 42 publications
0
32
2
Order By: Relevance
“…In the same way as the principal piece, the cytoskeleton associated with PM in the acrosomal region is mainly composed of spectrin/F-actin, but with the difference that it is remodeled during capacitation. During capacitation and AR, proteins associated with PM as well as with membrane lipids compartmentalize in the acrosome region; they are redistributed inside the acrosome or distribute towards the equatorial segment and postacrosomal region as well (Rochwerger & Cuasnicu 1992, Da Ros et al 2004, Selvaraj et al 2007, Tsai et al 2007, Pasten-Hidalgo et al 2008. These molecules in some way are maintained as compartmentalized in the acrosome before capacitation.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way as the principal piece, the cytoskeleton associated with PM in the acrosomal region is mainly composed of spectrin/F-actin, but with the difference that it is remodeled during capacitation. During capacitation and AR, proteins associated with PM as well as with membrane lipids compartmentalize in the acrosome region; they are redistributed inside the acrosome or distribute towards the equatorial segment and postacrosomal region as well (Rochwerger & Cuasnicu 1992, Da Ros et al 2004, Selvaraj et al 2007, Tsai et al 2007, Pasten-Hidalgo et al 2008. These molecules in some way are maintained as compartmentalized in the acrosome before capacitation.…”
Section: Discussionmentioning
confidence: 99%
“…However, those results will be presented in another report. The distribution of sperm surface antigens during capacitation and acrosome reaction has been well documented for proteins such as IZUMO1 (Sosnik et al 2009), CRISP1 (Da Ros et al 2004), and PH20 (Myles & Primakoff 1984), these proteins migrate after capacitation changing their localization. In a previous work, we have also shown that ADAM15 migrate from acrosome to the post-acrosomal region of mouse sperm before acrosome reaction (Pasten-Hidalgo et al 2008).…”
Section: P<0002mentioning
confidence: 99%
“…One possibility is that these domains are important for cell-surface binding and localization so as to target ICR domain actions. Evidence for this capacity comes from the fact that Crisp 1 binds to the mouse sperm surface in the epididymis and remains bound to the sperm in the female tract (Cohen et al 2000 ;Da Ros et al 2004 ;Roberts et al 2002Roberts et al , 2008. Its localization on the sperm and its binding lifetime are dependent on its glycosylation state.…”
Section: The Future Of Crisp Protein Relationships In Reproductionmentioning
confidence: 99%
“…The "D" form inhibits premature acrosome reaction in the male tract, but once in the female tract appears to unbind from the sperm during capacitation (Roberts et al 2008 ;Nixon et al 2006 ). In contrast, the "E" form of Crisp 1, having a different glycosylation pattern, binds to sperm in the epididymis, but is not easily removed even in the female tract (Da Ros et al 2004 ;Roberts et al 2008 ); rather, it migrates to the equatorial region of the sperm where it is thought to take part in sperm binding at the egg plasma membrane (Cohen et al 2008(Cohen et al , 2011.…”
Section: The Future Of Crisp Protein Relationships In Reproductionmentioning
confidence: 99%
See 1 more Smart Citation